2013
DOI: 10.1007/s11239-013-0919-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antiplatelet therapy in atherosclerotic disease: comparing the ASA low-response prevalence in CVD, CAD and PAD

Abstract: Although acetylsalicylic acid (ASA, aspirin) reduces the risk of ischemic events in patients with atherosclerosis, a substantial number of incidents continue to occur. As only limited data exist we evaluated the antiplatelet effectiveness of ASA in patients with different manifestations of atherosclerosis as in cerebrovascular, coronary artery and peripheral arterial disease (CVD, CAD, PAD). For the evaluation of the antiplatelet effectiveness of ASA we used whole blood aggregometry (Chrono-log Model 590). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…These inconsistencies are probably caused by differences in the characteristics of the original studies. Firstly, the predictive value of HTPR for clinical outcomes may be complicated because of multiple etiologies [42], as the roles of the platelet reactivity may be different in different vascular diseases (cardiovascular versus cerebrovascular), [43] or even different subtypes of ischemic stroke. [44][45][46] The stroke subtype was identified only in the study by Yi et al, but not in the study by Depta et al The sample was more homogeneous in the study by Yi et al, as only two subtypes were included: atherothrombotic or small artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies are probably caused by differences in the characteristics of the original studies. Firstly, the predictive value of HTPR for clinical outcomes may be complicated because of multiple etiologies [42], as the roles of the platelet reactivity may be different in different vascular diseases (cardiovascular versus cerebrovascular), [43] or even different subtypes of ischemic stroke. [44][45][46] The stroke subtype was identified only in the study by Yi et al, but not in the study by Depta et al The sample was more homogeneous in the study by Yi et al, as only two subtypes were included: atherothrombotic or small artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, as this study was not designed to assess clinical outcomes in patients with HTPR, one cannot conclude that one should use higher dose IV rather than oral aspirin in acute stroke. The same authors reported the results of another cross-sectional whole blood impedance aggregometry study in 737 patients with CVD, IHD or peripheral vascular disease (PVD) on 100-200 mg of oral aspirin or 500 mg of IV aspirin daily [47]. Aspirin doses ranged between 100 and 500 mg daily in the CVD subgroup [47].…”
Section: Platelet Aggregometrymentioning
confidence: 99%
“…The same authors reported the results of another cross-sectional whole blood impedance aggregometry study in 737 patients with CVD, IHD or peripheral vascular disease (PVD) on 100-200 mg of oral aspirin or 500 mg of IV aspirin daily [47]. Aspirin doses ranged between 100 and 500 mg daily in the CVD subgroup [47]. The prevalence of aspirin-HTPR was 28% in patients with CVD, 18% in those with IHD and 22% in those with PAD.…”
Section: Platelet Aggregometrymentioning
confidence: 99%
“…Guidelines for management of stroke recommend antiplatelet therapy for secondary prevention of noncardioembolic ischemic stroke, and accordingly, several antiplatelet agents including clopidogrel and aspirin are currently in use [1][2][3]. However, there are poor responders to aspirin and clopidogrel [4][5][6], who have high risk of major adverse cardiovascular events [7][8][9][10]. Approximately 19% of Japanese patients are CYP2C19 poor metabolizers (PM) who can only attain a low concentration of the active metabolite of clopidogrel [11].…”
Section: Introductionmentioning
confidence: 99%